Supramolecular hydrogen-bonded polyolefin elastomer/modified graphene nanocomposites with near infrared responsive shape memory and healing properties. (May 2015) - Kashif, Muhammad; Chang, Young-Wook
Graphical abstract: Highlights: Supramolecular hydrogen-bonded polyolefin elastomer/modified graphene nanocomposites were prepared via melt blending. Octadecylamine modified graphene sheets were dispersed at the nanoscale level in the elastomer matrix. Octadecylamine modified graphene acted as NIR-triggered nanoheaters as well as reinforcing filler for the elastomer matrix. Nanocomposites exhibit both shape memory and healing properties under NIR light exposure. Healing efficiency of the NIR-healed samples and thermally-healed samples are comparable. Abstract: Small amounts (0.25–1 wt%) of octadecylamine modified graphene oxide (ODA-GO) were incorporated into a 3-amio-1, 2, 4-triazole (ATA) crosslinked maleated polyethylene-octene elastomer (ATA-POE), a structurally dynamic supramolecular hydrogen-bonded thermoplastic elastomer, via melt blending to prepare ATA-POE/ODA-GO nanocomposites. Field-emission scanning electron microscopy and X-ray diffraction analysis for the ATA-POE/ODA-GO composites revealed that the ODA-GO sheets were dispersed at the nanoscale level in the elastomer matrix which results in enhancement of the mechanical properties of the nanocomposites at low filler loadings. These nanocomposites exhibit both shape memory and scratch-healing effects under near infrared (NIR) light exposure. It was revealed from the results that ODA-GO acted as NIR-triggered nanoheaters as well as reinforcing filler for the elastomer matrix.